FEATURES OF THE CLINICAL COURSE OF VIRAL HEPATITIS IN AGAINST THE BACKGROUND OF COMBINED HYMENOLEPIDOSIS - Usmanova E.M; Yusufjonov D.D; Axmadjonov D.E. (Scholar Express Journals, 2023)
Despite the great achievements for the study of hepatitis of viral etiology, today the WHO problem remains. In addition, concomitant diseases with viral hepatitis aggravates the course of the disease, leading to an adverse outcome. 80 patients with chronic viral hepatitis B were investigated from them in 47 patients with HVGV against the background of hymenolepidase. Higher indicators were revealed in patients with viral hepatitis in against the background of the concomitant course of hymenolepidosis, liver manifestations are more pronounced than in patients with viral hepatitis B without concomitant pathology, which is required to take into account when choosing a pathogenetic therapy tactics
Keywords: Viral hepatitis; chronic viral hepatitis B; hymenolepidosis